Kebebasan Berekspresi dalam Tekanan Regulasi: Studi terhadap Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) - Indriasari, Devi Tri (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2023)
This research aims to explain the implications of the implementation of the Electronic Information and Transaction Law (UU ITE) on freedom of expression and democracy in Indonesia. This research uses a qualitative approach with a case study method and is based on a post-positivistic paradigm. Data collection techniques were conducted through document analysis, in-depth interviews and observation. The research concludes that there is insufficient evidence to explain the background to the inclusion of several problematic articles into the ITE Law in 2008. The government and the House of Representatives originally prepared the ITE Bill to regulate electronic business transactions and pornography. However, at the last moment, articles with an authoritarian spirit were included. In addition, the implementation of this law has had the implication of inhibiting freedom of speech and expression in the virtual space and traumatizing victims to express their opinions on social media. Finally, civil society consistently rejects the ITE Law because it is misused to limit freedom of expression, which is part of democracy and human rights.